(untitled) (Revista do Centro de Estudos Portugueses, 1998)
Este artigo pretende analisar o papel do espetáculo e do voyeurismo em Stella Manhattan de Silviano Santiago. This paper presents an analysis of the importance of shows and voyeurism in Silviano Santiago’s Stella Manhattan.